Clinical and laboratory features of autoimmune hemolytic anemia associated with immune checkpoint inhibitors. Issue 5 (13th March 2019) - Leaf, Rebecca Karp; Ferreri, Christopher; Rangachari, Deepa; Mier, James; Witteles, Wesley; Ansstas, George; Anagnostou, Theodora; Zubiri, Leyre; Piotrowska, Zofia; Oo, Thein H.; Iberri, David; Yarchoan, Mark; et al.
Abstract: Immune checkpoint inhibitors (ICPis) are a novel class of immunotherapeutic agents that have revolutionized the treatment of cancer; however, these drugs can also cause a unique spectrum of autoimmune toxicity. Autoimmune hemolytic anemia (AIHA) is a rare, but often severe, complication of ICPis. We identified 14 patients from nine institutions across the United States who developed ICPi‐AIHA. The median interval from ICPi initiation to development of AIHA was 55 days (interquartile range [IQR], 22‐110 days). Results from the direct antiglobulin test (DAT) were available for 13 of 14 patients: 8 patients (62%) had a positive DAT and 5 (38%) had a negative DAT. The median pretreatment and nadir hemoglobin concentrations were 11.8 g/dL (IQR, 10.2‐12.9 g/dL) and 6.3 g/dL (IQR, 6.1‐8.0 g/dL), respectively. Four patients (29%) had a preexisting lymphoproliferative disorder, and two (14%) had a positive DAT prior to initiation of ICPi therapy. All patients were treated with glucocorticoids, with three requiring additional immunosuppressive therapy. Complete and partial recoveries of hemoglobin were achieved in 12 (86%) and 2 (14%) patients, respectively. Seven patients (50%) were rechallenged with ICPis, and one (14%) developed recurrent AIHA. Clinical and laboratory features of ICPi‐AIHA were similar in DAT positive and negative patients. ICPi‐AIHA shares many clinical features with primary AIHA; however, a unique aspect of ICPi‐AIHA is a high incidence of DAT negativity. Glucocorticoids are an effective first‐line treatment in the majority of patients with ICPi‐AIHA, and most patients who are rechallenged with an ICPi do not appear to develop recurrence of AIHA.